2022
DOI: 10.3389/fpls.2022.837528
|View full text |Cite
|
Sign up to set email alerts
|

Recent Advances in Understanding the Structural and Functional Evolution of FtsH Proteases

Abstract: The FtsH family of proteases are membrane-anchored, ATP-dependent, zinc metalloproteases. They are universally present in prokaryotes and the mitochondria and chloroplasts of eukaryotic cells. Most bacteria bear a single ftsH gene that produces hexameric homocomplexes with diverse house-keeping roles. However, in mitochondria, chloroplasts and cyanobacteria, multiple FtsH homologs form homo- and heterocomplexes with specialized functions in maintaining photosynthesis and respiration. The diversification of Fts… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 186 publications
0
12
0
Order By: Relevance
“…In our study, miR9410 targeted a filamentation temperature sensitive protein H 1 ( FtsH7 ) gene copy encoding a protease that in turns degrades D 1 protein in photosystem II. FtsH genes have been reported in tomato, sorghum, Arabidopsis and B. napus (Xu et al 2021 ; Yi et al 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…In our study, miR9410 targeted a filamentation temperature sensitive protein H 1 ( FtsH7 ) gene copy encoding a protease that in turns degrades D 1 protein in photosystem II. FtsH genes have been reported in tomato, sorghum, Arabidopsis and B. napus (Xu et al 2021 ; Yi et al 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…FtsH genes have been reported in tomato, sorghum, Arabidopsis and B . napus (Xu et al, 2021; Yi et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…In our study, miR9410 targeted a filamentation temperature sensitive protein H 1 ( FtsH7 ) gene copy encoding a protease that in turns degrades D1 protein in photosystem II. FtsH genes have been reported in tomato, sorghum, Arabidopsis and B. napus (Xu et al, 2021; Yi et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the genomes of putative tryptorubin producers, genomes of frequently used bacterial heterologous host strains were likewise mined for all genes annotated as proteases or peptidases to identify suitable host strains for subsequent heterologous expression studies of the putative minimal trp BGC. Phylogenetic analyses revealed that putative producers of tryptorubin‐like peptides encode members of four conserved protease families, three of which (M41 family of unassigned peptidases, [13] S16 family of unassigned peptidases [14] and AA223 family of peptidases [13] ) belong to the superfamily of AAA+ proteases that are intracellular, membrane‐associated enzymes that catalyze the degradation of a wide range of proteins. Moreover, members of the family of M24B unassigned extracellular metallo‐peptidases [15] were identified in all putative tryptorubin producers and all commonly used Streptomyces host strains (Figure S3).…”
Section: Figurementioning
confidence: 99%